Penerapan Media Kartu Huruf untuk Meningkatkan Kemampuan Membaca Permulaan Peserta Didik Kelas 1 SD Negeri Naikoten 2 - Tupu, Malfyen; Djuli, Labu; Sampe, Markus (Lembaga Yasin AlSys, 2025)
This study is motivated by the low early reading ability of first-grade students at SD Negeri Naikoten 2, where only 5 out of 27 students demonstrated good reading skills, while the remaining 22 were classified as low. The objective of the study is to improve early reading ability through the use of letter card media. A qualitative method was employed, with data collected through observation, interviews, tests, and documentation. Pre-cycle results showed that only 4 students (15%) met the competency standard, while 23 students (85%) did not. After implementing letter card media in Cycle I, the number of students who met the standard increased to 17 (63%), and in Cycle II, it further increased to 25 students (93%), leaving only 2 students (7%) who had not achieved mastery. These findings indicate a significant improvement from Cycle I to Cycle II, with more than 80% of students scoring above 70. The study concludes that letter card media is effective in enhancing the early reading ability of first-grade students. The implications of the study highlight the importance of teacher training in using simple yet effective learning media and provide opportunities for further research on the effectiveness of letter card media in different educational contexts.